Does Self-Efficacy and Emotional Control Protect Hospital Staff From COVID-19 Anxiety and PTSD Symptoms? Psychological Functioning of Hospital Staff After the Announcement of COVID-19 Coronavirus Pandemic - Bidzan, Monika; Bidzan-Bluma, Ilona; Szulman-Wardal, Aleksandra; Stueck, Marcus; Bidzan, Mariola (Frontiers in Psychology, 2020)
Objectives The aim of this study was to assess coronavirus disease 2019 (COVID-19) anxiety and posttraumatic stress disorder (PTSD) symptoms in the hospital staff, as well as to identify protective factors of COVID-19 anxiety once the coronavirus pandemic was announced in Poland. Methods 90 healthcare workers from the hospital in Poland completed validated self-report questionnaires assessing self-efficacy, emotional control, and PTSD symptoms; a questionnaire assessing COVID-19 anxiety; and a socio-demographic questionnaire. A multiple linear regression was conducted to assess the effects of gender, being directly vs indirectly exposed to patients, and general self-efficacy on COVID-19 anxiety. Results The analysis showed that female (β = −0.271, p < 0.01) healthcare professionals indirectly exposed to patients (β = −0.336, p < 0.01) and those who reported lower levels of general self-efficacy (β = −0.295, p < 0.01) have a stronger tendency to experience COVID-19 anxiety [R2 = 0.301, F(3,89) = 12.34, p < 0.01]. Conclusion The findings show the importance of self-efficacy for dealing with COVID-19 anxiety. The internal coping strategies should be introduced to healthcare workers.